Large-Scale Survey of Gut Microbiota Associated With MHE Via 16S rRNA-Based Pyrosequencing - Zhang, Zhigang; Zhai, Huiqin; Geng, Jiawei; Yu, Rui; Ren, Haiqing; Fan, Hong; Shi, Peng (The American journal of gastroenterology, 2013)
Elucidating the minimal hepatic encephalopathy (MHE)-associated gut microbiome may help in predicting and lowering the high risk for MHE in patients with cirrhosis. Twenty-six MHE patients were recruited and screened from among those with liver cirrhosis without overt hepatic encephalopathy as defined by abnormality seen on two test modalities: number connection test part A and the digit symbol test. Using 26 MHE-matched normal relatives and 25 cirrhotic patients without MHE as controls, by means of 16S ribosomal RNA (rRNA)-based pyrosequencing, we examined and analyzed 241,622 bacterial 16S rDNA gene sequences from feces of 77 subjects. Using multiple comparative analyses, our results found the continuous overrepresentation of two bacterial families, Streptococcaceae and Veillonellaceae, in cirrhotic patients with and without MHE, compared with normal individuals. In addition, we also discovered an MHE-unique interplay pattern of gut microbiota largely influenced by the members of those two families. Following these findings, we further revealed that gut urease-containing bacteria Streptococcus salivarius was absent in the normal group but was present in cirrhotic patients with and without MHE. The abundance of S. salivarius was significantly higher in cirrhotic patients with MHE than in those without (P=0.030), and the change in the amount of this bacteria was positively correlated with ammonia accumulation (R=0.58, P=0.003) in cirrhotic patients with MHE but not in those without. Gut microbiota dysbiosis may be associated with the presence of MHE in cirrhotic patients, in particular with ammonia-increasing phenotype in MHE. Gut ammonia-increasing bacteria S. salivarius might be expected to be a potential biomarker of ammonia-lowering therapies in cirrhotic patients with MHE.